2009
DOI: 10.1515/bot.2009.075
|View full text |Cite
|
Sign up to set email alerts
|

Microphytobenthic biomass along gradients of physical conditions in Arctic Kongsfjorden, Svalbard

Abstract: In contrast to numerous studies on the biomass of marine microphytobenthos from temperate coastal ecosystems, little is known from polar regions. Therefore, microphytobenthos biomass was measured at several coastal sites in Arctic Kongsfjorden (Spitsbergen) during the polar summer (June-August 2006). On sandy sediments, chla varied between 8 and 200 mg m -2 and was related to water depth, current/wave exposure and geographical location. Biomass was rather independent of abiotic parameters such as sediment prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…A halogen lamp (fibre optics of Leica MZ 6 binocular) was used as the light source. Studies of Glud et al (2002), Leu (2006) and Woelfel et al (2009a) as well as our values (Table 1) reported an average photon fluence density (PFD) of PAR of about 100 lmol photons m -2 s -1 at 5 m water depth in Kongsfjorden. Since most samples were taken at approximately 5 m water depth, our samples were equally irradiated with ca.…”
Section: Ex Situ Primary Productionsupporting
confidence: 82%
See 4 more Smart Citations
“…A halogen lamp (fibre optics of Leica MZ 6 binocular) was used as the light source. Studies of Glud et al (2002), Leu (2006) and Woelfel et al (2009a) as well as our values (Table 1) reported an average photon fluence density (PFD) of PAR of about 100 lmol photons m -2 s -1 at 5 m water depth in Kongsfjorden. Since most samples were taken at approximately 5 m water depth, our samples were equally irradiated with ca.…”
Section: Ex Situ Primary Productionsupporting
confidence: 82%
“…Decreasing in water transparency was observed in early June. In July, small changes in the vertical attenuation coefficients and PAR data (0.2-0.3; (Woelfel et al 2009a). Thus, light availability was rather similar at all sites down to 5 m water depth throughout the study period, except in the near vicinity of glaciers, where more turbid water was observed but not analysed.…”
Section: Study Site Sampling and Conditionsmentioning
confidence: 99%
See 3 more Smart Citations